2018
DOI: 10.1002/14651858.cd012256.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Final-impression techniques and materials for making complete and removable partial dentures

Abstract: We conclude that there is no clear evidence that one technique or material has a substantial advantage over another for making complete dentures and removable partial dentures. Available evidence for the relative benefits of different denture fabrication techniques and final-impression materials is limited and is of low or very low quality. More high-quality RCTs are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 93 publications
0
20
0
4
Order By: Relevance
“…There are numerous techniques for the final impressions making in the edentulous arches. [43][44][45][46][47] This clinical situation was complex because the patient had been wearing the existing complete dentures for the last 15 years and the residual alveolar ridges in the mandible were excessively reabsorbed and atrophied. Due to the short height of the ridge, it was decided to make the conventional final impression following the functional impression technique using her current complete dentures.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous techniques for the final impressions making in the edentulous arches. [43][44][45][46][47] This clinical situation was complex because the patient had been wearing the existing complete dentures for the last 15 years and the residual alveolar ridges in the mandible were excessively reabsorbed and atrophied. Due to the short height of the ridge, it was decided to make the conventional final impression following the functional impression technique using her current complete dentures.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is not a large number of studies comparing the one‐ and two‐step methods, two systematic reviews suggested that the two‐step impression procedure is not mandatory for achieving clinical success considering both denture quality and patients' perception of treatment, and the use of simpler and less costly methods may be sufficient to serve the needs of the majority of patients . A recent Cochrane review by Jayaraman et al reported that most of the randomised clinical trials on this topic were judged as having high risk of bias and concluded that “there is no clear evidence that one technique or material has a substantial advantage over another for making complete dentures and removable partial dentures” …”
Section: Discussionmentioning
confidence: 99%
“…Cochrane review by Jayaraman et al 35 reported that most of the randomised clinical trials on this topic were judged as having high risk of bias and concluded that "there is no clear evidence that one technique or material has a substantial advantage over another for making complete dentures and removable partial dentures". 35 Considering that there is no robust evidence that supports a generally recommendable protocol for complete denture impression in prosthodontic teaching and clinical practice, 7 the alternative protocol proposed in our study may combine the potential advantages of the two methods, including the simplification of the one-step procedure and the alleged higher quality of the reproduction of the denture-supporting area that is likely to be achieved in the two-step procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Eugenol, in combination with zinc oxide (ZOE), is one of the most common materials used as a root canal sealer in endodontics [1][2][3][4][5], as well as a pulp sedative in cases of pulpotomies [6][7][8][9] and an impression material for edentulous patients [10][11][12][13]. In restorative dentistry, ZOE cements are frequently applied as temporary materials during indirect restorations [14].…”
Section: Introductionmentioning
confidence: 99%